Analisis Yuridis terhadap Praktik Anti Suit Injunctions oleh Tiongkok Berdasarkan Agreement On Trips dalam Sengketa Hak Kekayaan Intelektual WTO (DS611) - Raul Jordy Fedayeen; Muhammad Happy Marcelino; Narendra Arya Fedhani Hartono; Ihsan Risqi Satria Winahyu; Muhammad Davin Zhia Ulhaq (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Anti-Suit Injunctions (ASIs) are defined as court orders prohibiting litigants from pursuing or initiating legal actions in the courts of other jurisdictions; they aim to manage parallel litigation and safeguard the integrity of domestic legal processes. In international trade, ASIs are crucial in disputes involving Standard-Essential Patents (SEPs) within high-tech sectors such as 5G, where the territorial nature of patents often triggers multi-forum litigation. This study employs a qualitative approach, focusing on legal interpretation and juridical argumentation regarding the provisions of the TRIPS Agreement and the WTO dispute settlement mechanism. The study finds that the practice of Anti-Suit Injunctions (ASIs) implemented by China has shifted from being merely a tool of civil procedure to a geoeconomic instrument influencing the enforcement of international patent rights. Although China justifies ASIs as a means to protect national jurisdiction, prevent forum shopping, and safeguard domestic economic interests, their implementation effectively restricts the ability of Standard-Essential Patent (SEP) holders to enforce their rights in the jurisdictions where the patents are valid, doing so through the threat of severe financial sanctions. Consequently, the legal status of ASIs in the DS611 case is best viewed as a practice potentially inconsistent with the principle of patent territoriality and the obligations regarding intellectual property rights enforcement set forth in Articles 28 and 41 of the TRIPS Agreement. This dispute demonstrates that national courts no longer function solely as forums for dispute resolution but also serve as strategic instruments to influence licensing negotiations and determine global technology valuations.